The Transformation of Jamaah Islamiyah and Actor Rationality: Implications of Rational Choice Theory for Deradicalization Strategies in Indonesia - Warsito Warsito (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2026)
This study examines the rationality behind the dissolution of Jemaah Islamiyah (JI) in Indonesia, employing the Rational Choice Theory framework. Unlike previous studies that focused primarily on ideological or security aspects, this research argues that JI's organizational transformation and eventual dissolution resulted from rational calculations by its members to evaluate risks, benefits, and social opportunities. Using a qualitative case study approach, data were collected through in-depth interviews, field observations, and documentation involving former JI members in the Greater Solo area. The findings reveal that the dissolution was not merely a consequence of government pressure but a product of internal rational considerations aimed at avoiding legal risks, safeguarding educational assets, and expanding socio-economic participation. The study identifies three forms of rationality operating within JI: ideological, pragmatic, and adaptive rationality. These findings suggest that ideological transformation within radical Islamic movements can be understood as a process of rational recalibration, rather than mere submission to external coercion. This study contributes to the understanding of deradicalization and social reintegration strategies in the Indonesian context.